Sosialisasi dan Pelatihan Penyusunan Pembukuan Sederhana Menggunakan Aplikasi Buku Warung Pada UMKM Mendoan - sari, Enita melisa; Nugraeni, Nugraeni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This community service activity aims to enhance the understanding of Micro, Small, and Medium Enterprises (MSMEs) in Pasar Bringharjo and Lippo Plaza Jogja regarding the importance of simple bookkeeping to support the sustainability of their businesses. Observations revealed that many MSME owners lacked knowledge on how to efficiently prepare financial records, particularly in tracking financial transactions. Therefore, direct assistance was provided through training on the use of the BukuWarung application, which helps MSME owners systematically create financial reports that are easy to understand. This activity was conducted in four sessions on March 26, April 2 and 26, and May 1, 2024. An evaluation of the program’s success was carried out on May 1, 2024, using questionnaires to measure MSME owners’ understanding of financial record-keeping and the use of the BukuWarung application. The evaluation results indicated that all MSME participants understood the importance of business financial reports, as well as how to record debt, income, and expenses using the BukuWarung application. Additionally, most MSME owners demonstrated a good grasp of the BukuWarung application as a whole and actively used it for business financial record-keeping. From the evaluation results, it can be concluded that this community service activity successfully addressed the financial record-keeping issues faced by MSME owners. This success is reflected in the increased understanding and application of better bookkeeping practices, which is expected to contribute to the sustainability of MSMEs in the Pasar Bringharjo and Lippo Plaza Jogja areas.